Small-scale opencast mining: an important research field for anthropogenic geomorphology - Byizigiro, R. Vaillant; Raab, Thomas; Maurer, Thomas (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Artisanal and small-scale mining (A&SM) is a growing economic sector in many third-world countries. This review focuses on anthropo-geomorphic factors and processes associated with small-scale opencast mining (SSOM), a form of A&SM in which near-surface ores are extracted by removing relatively thin covers of soil, bedrock or sediments. Being widespread and commonly conducted without proper planning and beyond the control of local authorities, this form of mining has potentially large impacts on landforms and landscape dynamics, often resulting in drastic consequences for the local environment and agriculture. SSOM should be regarded as a component of anthropogenic geomorphology because it involves the role of humans in creating landforms and modifying the operation of natural geomorphological processes, such as weathering, erosion, transport and deposition. By initiating new and modifying natural geomorphic processes, SSOM causes and/or accelerates geomorphic processes, resulting in various forms of land degradation. While the direct geomorphic impact of SSOM is in general easily discernible and leads to characteristic features, such as excavated pits and overburden spoil heaps, many secondary impacts are attributed to geomorphic processes triggered in the wake of the primary mining-induced landscape alterations. The magnitude of such secondary implications may well extend beyond the actual mining areas, but these effects have not been thoroughly addressed in the research so far. This review summarizes the known studies on the geomorphic impacts of SSOM operations and highlights common geomorphic processes and landforms associated with this type of anthropogenic activity, thus establishing a starting point for further in-depth research.